Spectrophotometrioc Determination of Cefixime Trihydrate - Shankar, D.G.; Sushma, K.; Lakshmi, R.V.; Srinivasa Rao, Y.; Reddy, M.N.; Murthy, T.K. (Asian Journal of Chemistry, 2010)
Two simple, sensitive and selective methods have been developed for the determination of cefixime in pure and pharmaceutical preparations. Method A is based on the formation of green coloured chromogen by ox-idative coupling reaction with 3-methyl-2- bezothiazolinone hydrazone (MBTH) and ferric chloride having absorption maximum at 620 nm, whereas method B is based on the reduction and complex formation with ferric chloride and 1,10- phenanthroline which exhibit maximum absorption at 510 nm. These methods obey Beer's law in the concentration range of 1 to 15 μg/mL and 0.2 to 6 μg/mL respectively. The methods are statistically evaluated for accuracy and precision.